(untitled) (Journal of Engineering, 2010)
Analytical model is used in this paper to predict the load carrying capacity of structural concrete members under flexural and normal force which can be concentric or eccentric. The analysis is based on requirement of equilibrium and compatibility of strain in concrete and steel or FRP. The adopted model is based on the real stress strain diagrams for materials. In accordance with this model, the member cross section is covered by a mesh with the smallest cells. After that, stress or strain is determined in each cell and the integral is substituted by the process of summation to define the elements of stiffness matrix. The force vectors equations have nonlinear behaviour. However, in this model, these nonlinear equations are changed to linear equations using the iteration methods with fixity of secant modulus of elasticity in each iteration cycle. In this paper. FORTRAN computer program language is used to compute the force and strains vectors. The comparison between the analytical resaks obtained from the used model and experimental data for other researchers is performed. The analytical model is giving a reasonable agreement between the theoretical and experimental results.